Implementation of Novel Methods, Markers or Sample types in Molecular Pathology – Quality Assurance Aspects - Keppens, Cleo; Smedt, Jan De; Dequeker, Elisabeth MC (Archives of Clinical and Biomedical Research, 2020)
Molecular pathology is continuously evolving and laboratories are challenged to implement tests accurately prior to administration of targeted therapies. External quality assessment (EQA) programs revealed method-specific problems for laboratories who switched methods, and a good adherence to guidelines during method validation/verification in the USA. This study evaluated current guideline adherence in Europe and experienced hurdles during test, marker or sample implementation. EQA participants from the European Society of Pathology were invited to complete an electronic survey if they: (i) recently changed their assay, (ii) implemented PD-L1 analysis, (iii) or introduced analysis of circulating tumor DNA. In total, survey data from 54 laboratories was analyzed. The majority of laboratories implemented a written procedure for validation (68.5%) or verification (59.3%), in 53.7% and 44.4% cases based on standards or available literature. For 20.4% of respondents, a specific guideline was not available yet for their test strategy. Method revalidations and staff training, as well as EQA participation were frequently performed. Most reported hurdles included controlling of pre-analytical variables (87.0%), finding appropriate controls for rare mutations or antigens, and for varying positivity ranges/frequency (56.5%). In the post-analytical phase, interpretation of complex bio-informatics was a main concern (70.0%), while staff limitations, increased costs and workload (53.1%-57.1%) were barriers affecting the entire test process. Documentation of procedures and guideline adherence was higher but not limited to accredited institutes. The data stressed the importance of further quality efforts to aid laboratories with controlling pre-analytical variables, the selection of appropriate controls, and test interpretation of complex data.